Biological, ecological and faunistic aspects of the aquatic coleoptera from Laguna de los Padres integral reserve and Paititi private natural reserve (General Pueyrredón district, Buenos Aires province) and its value in the local conservation - Macchia, Gabriel Alejandro (2023)
The district of General Pueyrredon has a high diversity of environments from the montane range environments belonging to the south oriental zone of the Tandilia System to the coastal and grasslands landscapes. A series of samples was carried out in two protected areas associated to the Tandilia System: Laguna de Los Padres Integral Reserve and Paititi Private Natural Reserve, collecting in both sites a total of 41 species belonging to 9 families of aquatic coleoptera. This work is the first in record the aquatic beetle fauna to the water bodies associated to these environments. As a result of this, two species are cited for the first time to Buenos Aires province: Vatellus wheeleri Miller, 2005 (Dytiscidae) and Suphisellus variicollis Zimmermann, 1921 (Noteridae). Also, the seasonal phenologies of several species are published for the first time.